Characterization of water reservoirs affected by acid mine drainage: geochemical, mineralogical, and biological (diatoms) properties of the water - Valente, Teresa Maria Fernandes (2016)
This work presents a combination of geochemical, mineralogical, and biological data obtained in water reservoirs located in one of the most paradigmatic mining regions, suffering from acid mine drainage (AMD) problems: the Iberian Pyrite Belt (IPB). Four water reservoirs located in the Spanish sector of the IBP, storing water for different purposes, were selected to achieve an environmental classification based on the effects of AMD: two mining dams (Gossan and Águas Ácidas), a reservoir for industrial use (Sancho), and one with water used for human supply (Andévalo). The results indicated that the four reservoirs are subject to the effect of metallic loads from polluted rivers, although with different levels: Águas Ácidas > Gossan > Sancho ≥ Andévalo. In accordance, epipsammic diatom communities have differences in the respective composition and dominant taxa. The dominant diatoms in each reservoir indicated acid water: Pinnularia acidophila and Pinnularia aljustrelica were found in the most acidic dams (Gossan and Águas Ácidas, with pH <3), Pinnularia subcapitata in Sancho (pH 2.48-5.82), and Eunotia exigua in Andévalo (pH 2.34-6.15).